Implementation of The Basic Freedom of Contract in Review From The Shariah Alliance - Ulfanora (Master of Law Program, Ekasakti University, 2024)
In civil matters, the parties will not be separated from the legal relationship. The legal relationship itself arises when there are rights and obligations of the parties so that what is agreed can be achieved. The parties are given freedom to make a contract. The contract itself must meet both subjective and objective requirements. One of the subjective conditions, which is the agreement between the parties, must be based on the principle of freedom of contract. The basis of freedom of contract according to Article 1338 BW